Diabetes mellitus: novos alvos terapêuticos - Franciscon, Julia Ferretto (My University, 2025)
Diabetes Mellitus (DM) is a complex and progressive metabolic disorder characterized by insulin resistance, beta-cell dysfunction, and wide-ranging metabolic disturbances that favor the development of chronic complications. Although established therapies such as insulin, metformin, and sulfonylureas remain essential, many patients fail to achieve adequate glycemic targets or experience significant adverse effects, reinforcing the need for new therapeutic approaches. This work aimed to identify, analyze, and synthesize recent evidence on new drugs and emerging therapeutic strategies for the treatment of Diabetes Mellitus, highlighting their efficacy, safety, and potential clinical application in improving metabolic control. This integrative review analyzed studies published between 2020 and 2024 investigating novel drugs and emerging strategies for diabetes management. A structured search conducted exclusively in PubMed identified 68 studies, of which 20 met all eligibility criteria after screening and full-text evaluation. The findings demonstrate substantial advances in innovative therapeutic classes, including GLP-1 receptor agonists, SGLT2 inhibitors, DPP-4 inhibitors, antivirals with disease-modifying potential, combination therapies, and metabolic adjuvant interventions. Key results include partial preservation of beta-cell function with pleconaril plus ribavirin in new-onset type 1 diabetes; enhanced glycemic and weight outcomes with liraglutide; efficacy of remogliflozin as a new SGLT2 inhibitor; metabolic advantages of triple therapy with dapagliflozin plus sitagliptin plus metformin XR; and promising adjuvants such as Crocus sativus extract, photobiomodulation, and gut-modulating agents. Despite encouraging evidence, limitations such as small sample sizes, short follow-up periods, and methodological heterogeneity warrant cautious interpretation. Overall, emerging molecules and combination therapies expand therapeutic possibilities, offering potential improvements in glycemic control, reduction of complications, and more personalized management of DM. [resumo publicado pelo autor]
O Diabetes Mellitus (DM) é uma condição metabólica complexa e progressiva, cuja fisiopatologia envolve resistência à insulina, disfunção das células beta e alterações metabólicas amplas que contribuem para complicações crônicas. Apesar da disponibilidade de terapias consolidadas, como insulina, biguanidas e sulfonilureias, muitos pacientes não atingem metas glicêmicas adequadas ou apresentam efeitos adversos significativos, o que impulsiona a busca por novas abordagens terapêuticas. Tem como objetivo identificar, analisar e sintetizar as evidências recentes sobre novos fármacos e estratégias terapêuticas emergentes para o tratamento do Diabetes Mellitus, destacando sua eficácia, segurança e potencial aplicação clínica no aprimoramento do controle metabólico. Esta revisão integrativa analisou artigos publicados entre 2020 e 2024 que investigam novos fármacos e estratégias emergentes para o tratamento do diabetes. A busca realizada exclusivamente na base PubMed identificou 68 estudos, dos quais 20 atenderam aos critérios de inclusão após triagem e leitura crítica. Os resultados evidenciam avanços substanciais em classes terapêuticas inovadoras, como agonistas do receptor GLP-1, inibidores de SGLT2, inibidores de DPP-4, antivirais com potencial modificador de doença, terapias combinadas e intervenções metabólicas adjuvantes. Entre os achados mais relevantes, destacam-se a preservação parcial da função beta no uso de pleconaril mais ribavirina em DM1; benefícios glicêmicos e ponderais superiores com liraglutida; eficácia de remogliflozina como novo SGLT2; vantagens metabólicas de combinações como dapagliflozina mais sitagliptina mais metformina XR; além de potenciais adjuvantes como Crocus sativus, fotobiomodulação e moduladores intestinais. Apesar dos resultados promissores, limitações como amostras reduzidas, curta duração de seguimento e heterogeneidade metodológica exigem cautela. Conclui-se que novas moléculas e terapias combinadas ampliam o arsenal terapêutico, com potencial para melhorar o controle glicêmico, reduzir complicações e favorecer abordagens mais personalizadas no manejo do DM. [resumo fornecido pelo autor]
Keywords: Diabetes; Terapêutica; Controle glicêmico; Insulina